In the footsteps of Einstein, Sagan and Barnard: Identifying South Africa’s most visible scientists - Joubert, Marina; Guenther, Lars (South African Journal of Science, 2017)
Highly visible scientists are increasingly recognised as influential leaders with a special role to play in making science part of mainstream society. Through consultation with a panel of 45 experts working at the science–media interface, we sought to identify the most visible scientists currently living and working in South Africa. In total, 211 scientists – less than 1% of the scientific workforce of the country – were identified as visible in the public sphere. The demographic profile and institutional spread of South Africa’s visible scientists suggest that more should be done to increase the diversity of scientists who are publicly visible. Although only 8% of South Africans are white, 78% of the group of visible scientists were white, and 63% of the visible scientists were men. Only 17 black women were identified as publicly visible scientists. While visible scientists were identified at 42 different research institutions, more than half of the visible scientists were associated with just four universities. Recent controversies surrounding the two most visible South African scientists identified via this study, and the potential implications for fellow scientists’ involvement in public engagement, are briefly discussed. Significance: • This is the first study to identify highly visible scientists in South Africa. • The study has meaningful policy implications for mobilising scientists towards public science engagement. • It is an important contribution towards the new public engagement framework of the Department of Science and Technology.